Identifying and Addressing Students’ Fears in Preaching (Homiletic, 2025)
What can be done for student preachers who are afraid to preach? To determine an answer to that question, this paper considers a body of research into a phenomenon called communication apprehension (CA). In so doing, it provides practical help for teachers of preaching that they might improve their ability to identify students who are afraid, understand more deeply the possible causes of their students' fears, understand the effect of fear on their students' sermon delivery and ministry career; and finally, acquire practical skills for alleviating their students' apprehension when stepping into the classroom pulpit.